From torrents to trickles: Irrigation's future in Africa and Asia - Ringler, Claudia (Annual Reviews, 2021)
Irrigation has been a key component of agricultural intensification and transformation in Asia and has the potential to take on the same role in Sub-Saharan Africa. Irrigation has contributed to increased food production, lower food prices, higher rural employment, and overall agricultural and economic growth. At the same time, irrigation—through its large consumptive water use—has accelerated water depletion, degradation, and pollution; moreover, it has benefitted richer farmers more than poorer farmers. This article reviews the contributions and challenges of irrigation and identifies a series of measures to increase the sustainability and equity of irrigation going forward.